Culture and customs of Korea - Clark, Donald N. (Culture and customs of Asia., 2000)
For centuries, although strongly influenced by the Chinese, Koreans have maintained a unique civilization with their own language, social organization, food, national costume, political institutions, and customs. The disruptions of the 20th century have included a long and difficult period of foreign rule and a devastating civil war. However, Koreans continue to prize their traditional culture, and the younger generations have embraced Koreanness with a determination to assert Korea's place in the world. Culture and Customs of Korea artfully depicts the past and present in North and South Korea with chapters on the story of the Korean people, thought and religion, arts and literature, performing arts, daily life and folkways, life in a Korean village, life in urban Korean, and gender, marriage, and the lives of Korean women. A chronology and glossary supplement the text.